Analisis Faktor-Faktor yang Mempengaruhi Kualitas Pelayanan dan Promosi serta Minat Nasabah dalam Memutuskan Menabung di Bank Danamon Simpan Pinjam Unit Pemalang - Putranto Hari Widodo; Suripto Suripto (JBIMA (Jurnal Bisnis dan Manajemen), 2016)
This study entitled “Analysis of The Factors Affecting The Quality of Services and The Promotion and Customers' Interest in Deciding Savings in Bank Savings and Loans Unit Danamon Pemalang” (The case study of danamon bank saving and loan unit pemalang). The purpose of this study was to determine and analyze the effect of significantly variable location of the decision customer savings, promotion to the decision variable customer savings, variable interest rate decision to customer savings and variable service to the customer savings decision. In this research using accidental sampling method, which is a technique-based sample determination or spontaneity factor coincidence and random sampling method, namely sampling on the basis of certain considerations, among respondents who are customers of the institution at least 1 year. The testing in this study conducted by validity, reliability, classical assumptions, multiple linear analysis and hypothesis testing in the form of t test and F test. With multiple linear regression analysis in this study showed b1 = -0.129 variables showed a negative influence Location (X1) to the Customer Decision Saving, b2 = 0,016 variables showed significant influence Promotion (X2) to the Customer Decision Saving, b3 = 0.757 show influence a significant variable interest rate (X3) against Decision Customer Savings and b4 = -0.094 variables showed a negative influence Services (X4) against Decision Customer Savings. To test the hypothesis partially used t test, obtained tcount for variable location (X1) is -1.759, variable Promotions (X2) of 0.178, a variable interest rate (X3) of 8.528 and a variable Services (X4) of -0.654 with criteria t tabel amounting to 1,990 were used in this test. From the F test results obtained Fcount 20.046 with a significance level of 0.000 was much smaller than 0.05 and greater than Ftable of 2.49. Determinant coefficient (R2) of 51.0%, which means that the variable Saving Decision Customer Area affected by variable factors, variables Promotion, variable interest rate and variable service while the remaining 49.0% is influenced by other factors outside the model equations.